The prevalence and personal factors related to musculoskeletal disorders in occupational van drivers: a case study of public transport center in Hatyai, Songkhla. - Nachaya Sea-jern, Nachaya; Pochana, Klangduen; Sungkhapong, Angoon (Asia-Pacific Journal of Science and Technology, 2017)
A cross-sectional study was conducted to investigate the prevalence of musculoskeletal disorders (MSDs) and personal factors affecting musculoskeletal disorders among public van drivers in Hatyai, Songkhla, Thailand. A total of 164 male drivers were involved in this study. Information on personal data was collected by face-to-face interviews. The prevalence of musculoskeletal disorders symptoms was assessed using the modified Standardized Nordic Question-naire for The Analysis of Musculoskeletal Symptoms. The relationship of factors was analyzed by using chi-square and odds ratio. The result showed that the average age of drivers was 44.09 years old and the Body Mass Index (BMI) was 23.83 kg/m 2 . The maximum prevalence of MSDs in the last seven days were lower back (29.26%, 95% CI: 22.43-36.86), neck (13.41%, 95% CI: 8.60-19.60) and shoulder (11.58%, 95% CI: 7.12-17.49), respectively. The maximum prevalence of MSDs in the last twelve months were lower back (62.19%, 95% CI: 54.30-69.63) neck (23.78%, 95% CI: 17.48-31.04) and shoulder (23.78%, 95% CI: 17.48-31.04), respectively. From the analysis, it was found personal factor had significantly related to the occurrence of musculoskeletal disorders in the van drivers. The relevance personal factors were BMI, BSA, alcohol consumption and previous record on back pain. The study found the comparatively high prevalence of musculoskeletal disorders in public van drivers. Therefore, the prevention of the risk of musculosk-eletal disorders in occupational drivers should be taken into serious actions in order to improve road safety.